Slo1 deficiency impaired skeletal muscle regeneration and slow‐twitch fibre formation - Chao Xia; Yonghui Wang; Tianyuan Jiang; Yan Hu; Yang Chen; Xinrun Ma; Xuemei Zhang; Yanhong Gao (Wiley, 2023)
Abstract Background It has been observed that Slo1 knockout mice have reduced motor function, and people with certain Slo1 mutations have movement problems, but there is no answer whether the movement disorder is caused by the loss of Slo1 in the nervous system, or skeletal muscle, or both. Here, to ascertain in which tissues Slo1 functions to regulate motor function and offer deeper insight in treating related movement disorder, we generated skeletal muscle‐specific Slo1 knockout mice, studied the functional changes in Slo1‐deficient skeletal muscle and explored the underlying mechanism. Methods We used skeletal muscle‐specific Slo1 knockout mice (Myf5‐Cre; Slo1flox/flox mice, called CKO) as in vivo models to examine the role of Slo1 in muscle growth and muscle regeneration. The forelimb grip strength test was used to assess skeletal muscle function and treadmill exhaustion test was used to test whole‐body endurance. Mouse primary myoblasts derived from CKO (myoblast/CKO) mice were used to extend the findings to in vitro effects on myoblast differentiation and fusion. Quantitative real‐time PCR, western blot and immunofluorescence approaches were used to analyse Slo1 expression during myoblast differentiation and muscle regeneration. To investigate the involvement of genes in the regulation of muscle dysfunction induced by Slo1 deletion, RNA‐seq analysis was performed in primary myoblasts. Immunoprecipitation and mass spectrometry were used to identify the protein interacting with Slo1. A dual‐luciferase reporter assay was used to identify whether Slo1 deletion affects NFAT activity. Results We found that the body weight and size of CKO mice were not significantly different from those of Slo1flox/flox mice (called WT). Deficiency of Slo1 in muscles leads to reduced endurance (~30% reduction, P < 0.05) and strength (~30% reduction, P < 0.001). Although there was no difference in the general morphology of the muscles, electron microscopy revealed a considerable reduction in the content of mitochondria in the soleus muscle (~40% reduction, P < 0.01). We found that Slo1 was expressed mainly on the cell membrane and showed higher expression in slow‐twitch fibres. Slo1 protein expression is progressively reduced during muscle postnatal development and regeneration after injury, and the expression is strongly reduced during myoblast differentiation. Slo1 deletion impaired myoblast differentiation and slow‐twitch fibre formation. Mechanistically, RNA‐seq analysis showed that Slo1 influences the expression of genes related to myogenic differentiation and slow‐twitch fibre formation. Slo1 interacts with FAK to influence myogenic differentiation, and Slo1 deletion diminishes NFAT activity. Conclusions Our data reveal that Slo1 deficiency impaired skeletal muscle regeneration and slow‐twitch fibre formation.